Truth and realism - Greenough, Patrick; Lynch, Michael P. (Michael Patrick), 1966- (Oxford : Clarendon, 2006)
Is truth objective or relative? What exists independently of our minds? The essays in this book debate these two questions, which are among the oldest of philosophical issues and have vexed almost every major philosopher, from Plato, to Kant, to Wittgenstein.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Realism; Relativity